False Results in Urine Drug Screen for Amphetamine, Methamphetamine, and Ecstasy: A Systematic Review - Zahra Babazadeh Igdir; Mohammad Delirrad; Adel Ghorani-Azam (Archives of Pathology & Laboratory Medicine, 2026)
Context.— Amphetamines and methamphetamines are used for their hallucinogenic and euphoric effects. Owing to structural similarity of the drugs and lack of specificity in antibody-based drug screening methods, these tests are associated with false results, which can lead to misinterpretation with catastrophic consequences. Objective.— To summarize all drugs and chemicals that can lead to false-positive and false-negative test results for amphetamine and methamphetamine. Data Sources.— A systematic literature search was performed on February 2025 to find drugs and chemicals that can produce false results in urine toxicology tests for amphetamines and methamphetamine. For this purpose, “false result,” “urine screening,” and “amphetamine and methylamphetamine” with different spellings and similar terms were searched in the title, keywords, and abstract of articles. The data were then collected and described qualitatively. Conclusions.— The data from 92 included studies showed that nearly 100 different drugs and chemicals can interfere with immunoassay tests of amphetamine and methylamphetamine, leading to false results. The most prominent drugs that lead to false results even at therapeutic doses include antidepressants, antipsychotics, antihistamines, antibiotics, gastrointestinal medications, and drugs used to treat upper respiratory tract infection and cardiovascular diseases. Findings also showed that some acids and alkalis are important external factors affecting the results of screening tests. The results of urine screening tests for amphetamines and methamphetamines should be considered as the initial screening result; however, the results should be interpreted according to the drug history of patients. Also, confirmatory test should confirm both positive and negative results.